Socio-economic and reproductive concomitants of abdominal adiposity and hypertension: A study on Bengali-speaking Hindu women of Habra, North 24 Parganas, West Bengal, India - Debnath, Samarpita; Mallick, Akash; Ghosh, Anushka; Basu, Ipsita; Bandopadhyay, Arup Ratan (Anthropological Review, 2020)
Obesity and hypertension have become a global epidemic among the women, especially as they experience additional stressful events compared to men. The epidemiology of these two metabolic disorders is regulated by various biological, socio-economic, reproductive and lifestyle factors related to women. However, inconsistency in the nature and magnitude of the effects of these traits indicates exploring the areas where little emphasis has been given. In this context, the present study attempted to determine the effect of socio-economic and reproductive traits on hypertension and abdominal adiposity among women living in the North 24 Parganas district of West Bengal, India. Data on socio-demographic and reproductive traits were collected from 319 adult women from both rural and urban sectors of Habra block I. Anthropometric measurements and Blood pressure levels were measured following standard protocols. Results highlighted that the prevalence of obese individuals and hypertensive individuals were 73.4 and 50.5 per cent respectively. Women with low income (OR=0.51) were at lower risk and post-menopausal women (OR=1.71) were at higher risk of developing abdominal adiposity. The risk of developing hypertension increased with higher educational attainment (OR=2.43). Post-menopausal women (OR=0.46) and shifting workers (OR=0.40) were at lower risk of developing hypertension. The risk also decreased with increased age (OR=0.96). Present study revealed that menopause is a significant event to predict abdominal adiposity and hypertension among Bengali-speaking Hindu women.